A Coupled Soil Water Balance Model for Simulating Depression‐Focused Groundwater Recharge. Issue 1 (27th September 2018) - Noorduijn, Saskia L.; Hayashi, Masaki; Mohammed, Getachew A.; Mohammed, Aaron A.
Abstract : Core Ideas: Ephemeral ponds in depressions are the foci of groundwater recharge in the Canadian Prairies. Freeze–thaw processes influence snowmelt runoff and depression‐focused recharge. A new water balance model was developed to represent these processes. The water balance model successfully simulated the observed soil processes. This model will provide a tool to estimate recharge in the prairie landscape. In arid and semiarid environments, focused infiltration of rain and snowmelt water under topographic depressions is an important mechanism of groundwater recharge. Quantifying the aggregated recharge from numerous small depressions is a major challenge in water resource management. Building on field‐based investigations into the surface water–groundwater interaction of individual depressions and their catchments (i.e., uplands) in the Canadian Prairies, we have developed a simple water balance model to simulate groundwater recharge considering the hydrological coupling of a depression–upland system. The model is based on the Versatile Soil Moisture Budget (VSMB), which has been widely used in the Canadian Prairies to simulate soil moisture conditions. We evaluated the new model, VSMB Depression‐Upland System (VSMB‐DUS), using field data consisting of an artificial flooding experiment and long‐term monitoring of a depression in Alberta, Canada. The model captured surface water level, soil moisture, and groundwater responses to the artificial flooding with reasonable accuracy and represented the interannual variability of recharge fluxes during a 5‐yr period (2007–2011), including dry and wet years. Simulated annual recharge varied between 12 and 45 mm, and annual precipitation varied between 453 and 597 mm during the 5‐yr period. The VSMB‐DUS tends to over‐ or underestimate snowmelt runoff in individual years; however, simulated recharge was only slightly affected by the errors in snowmelt runoff estimation. Due to its computational efficiency and robust algorithms, the VSMB‐DUS will provide a useful tool for estimating aggregated recharge in a large‐scale model grid cell containing hundreds of depression‐upland systems.